Detection Character Caged Civet of Robusta Coffee Temanggung - Laela Nur Rokhmah; Sri Mulyani (Universitas PGRI Semarang, 2020)
The demand for coffee is currently increasing. Apart from health reasons, it is also because of life style or lifestyle. This includes the demand for civet coffee. Increasing demand both from within the country and abroad due to the unique taste. Increasing luwak production can be done by producing coffee using luwak tangkar. In this study, civets were used individually and given coffee once in the afternoon. The rest is given rice, bananas and meat. This study aims to determine the taste of Temanggung civet and natural robusta coffee. This study used 25 untrained panelists. From this research, Robusta Temanggung which was processed using fermented fermented luwak for 12 hours showed sensoryly that untrained panelists could notice a striking difference between the two. The difference lies in the medium body, higher acidity, and lower bitterness in civet coffee.